"Down in the Sewers": Perceptions of Depression and Depression Care Among African American Men. Issue 1 (January 2018) - Hudson, Darrell L.; Eaton, Jake; Banks, Andrae; Sewell, Whitney; Neighbors, Harold
Depression is one of the most common, costly, and debilitating psychiatric disorders in the United States. One of the most persistent mental health disparities is the underutilization of treatment services among African American men with depression. Little is known about appropriateness or acceptability of depression care among African American men. The purpose of this study was to examine perceptions of depression and determine barriers to depression treatment among African American men. A series of four focus groups were conducted with 26 African American men. The average age of the sample was 41 years and most participants reported that they had completed high school. Nearly half of the participants reported that they are currently unemployed and most had never been married. The most common descriptions of depression in this study were defining depression as feeling down, stressed, and isolated. A small group of participants expressed disbelief of depression. The majority of participants recognized the need to identify depression and were supportive of depression treatment. Nonetheless, most men in this sample had never sought treatment for depression and discussed a number of barriers to depression care including norms of masculinity, mistrust of the health care system, and affordability of treatment. Men also voiced their desire to discuss stress in nonjudgmental support groups. Research findings highlight the need to increase the awareness of symptoms some African American men display and the need to provide appropriate depression treatment options to African American men.